The current landscape of personalised preventive approaches for non-communicable diseases: A scoping review - Sara Farina; Tommaso Osti; Luigi Russo; Alessandra Maio; Nicolò Scarsi; Cosimo Savoia; Abdelrahman Taha; Leonardo Villani; Roberta Pastorino; Stefania Boccia (PLoS ONE, 2025)
Introduction Personalised prevention offers a promising tool to reduce the impact of non-communicable diseases, which represent a growing health burden worldwide. However, to support the adoption of this innovation it is needed to clarify the current state of available evidence in this area. This work aims to provide an overview of recent publications on personalised prevention for chronic conditions. Materials and methods A scoping review of scientific literature from Medline, Scopus, Web of Science and grey literature was conducted. Eligible articles included prospective primary studies and clinical practice directives on personalised preventive approaches for chronic diseases published between January 2017 to December 2023. The review followed Arksey-O’Malley guidelines and PRISMA-ScR checklist. Results We identified 121 publications including 60 primary cohort studies and 61 clinical practice directives. We extracted 249 personalised preventive approaches, 27% in primary prevention, 27% in secondary prevention, and 46% in tertiary prevention. In primary prevention, 50% of the 67 approaches were from cohort studies, mainly targeting cardiovascular diseases, and 50% from directives primarily focused on cancer. Secondary prevention included 66 approaches, 73% from directives mainly concerning breast cancer. Tertiary prevention included 116 approaches, evenly distributed among the two publication types and focusing mostly on cancer and cardiovascular diseases. Lastly, tertiary prevention is the most represented level of prevention both in primary research studies and directives (54% and 41% respectively). Conclusions Our study highlights a significant focus on personalised prevention in oncology in the past few years, with numerous recently issued clinical practice directives. We identified substantial original research in personalised primary prevention of cardiovascular diseases, indicating growing interest in the field. However, the distribution of primary studies and directives across the three preventive levels anticipate challenges in generating evidence of clinical utility in primary and secondary prevention, with most approaches falling under tertiary prevention.